An improved predictive control for parallel grid-connected doubly fed induction generator-based wind systems under unbalanced grid conditions. Issue 4 (August 2019) - Ghodbane-Cherif, Meriem; Skander-Mustapha, Sondes; Slama-Belkhodja, Ilhem
Recently, the massive integration of renewable energy sources, especially wind and solar ones, has attracted researchers to new issues such as power quality. In this context, this article deals with an improved deadbeat predictive control for parallel grid-connected doubly fed induction generator-based wind systems under unbalanced grid conditions. The impact of an asymmetrical voltage sag has been treated for a doubly fed induction generator- wind system with emphasis on the occurrence of the negative current. In the case of a micro-grid based on wind systems, the effect of this current increases with the line impedance and thereby the system location. An improved predictive deadbeat control technique is proposed for the rotor side converter to enhance the behaviour of the wind system. A dynamic modelling of the doubly fed induction generator in both positive and negative reference frames has been proposed to focus on the behaviour of the system for these various operating conditions. Results of different simulation scenarios prove the effectiveness of the proposed improved predictive deadbeat control.